Search
Ask a question
0

Rearrange the equation to make x the subject

Y=x2-2x-3

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Michael J. | Effective High School STEM Tutor & CUNY Math Peer LeaderEffective High School STEM Tutor & CUNY ...
5.0 5.0 (5 lesson ratings) (5)
0
You have to solve for x.
 
 
Add 3 to both sides of the equation.
 
Y + 3 = x2 - 2x
 
 
Add 1 to both sides of the equation.
 
Y + 4 = x2 - 2x + 1
 
Y + 4 = (x - 1)2
 
 
Square-root both sides of the equation.
 
±√(Y + 4) = x - 1
 
 
Add 1 to both sides of the equation..
 
1 ± √(Y + 4) = x